2013
DOI: 10.5402/2013/595789
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Vacuum-Assisted Closure and Its Modifications: A Review

Abstract: Negative topical pressure, the general category to which the trademarked VAC therapy belongs, is not a new concept in wound therapy. It is also called subatmospheric pressure therapy, vacuum sealing, vacuum-assisted closure therapy, vacuum pack therapy, and sealing aspirative therapy. The VAC therapy system is trademarked by Kinetic Concepts, Inc., or KCI. It was first reported in 1997. The aim of the procedure is to use negative pressure to create suction, which drains the wound of exudate (i.e., fluid, cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…There are numerous trials done so far based on various variables all of which are aiming for a better faster healing, with an acceptable risk during treatment. 7 The mechanisms of action that can be attributed to NPWT therapy are an increase in blood flow-perfusion (human and animal studies), Promotion of angiogenesis (animal studies only), granulation tissue formation, Reduction in the wound surface area of several types of wounds (chronic) but not all wounds (acute), A positive modulation of the inhibitory contents in the wound fluid, there is an induction of cell proliferation (in vitro and animal studies only), reduction of oedema and bacterial clearance, removal of exudates. 8 In short it is a fact that VAC therapy, is a faster more effective and clinically proven wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous trials done so far based on various variables all of which are aiming for a better faster healing, with an acceptable risk during treatment. 7 The mechanisms of action that can be attributed to NPWT therapy are an increase in blood flow-perfusion (human and animal studies), Promotion of angiogenesis (animal studies only), granulation tissue formation, Reduction in the wound surface area of several types of wounds (chronic) but not all wounds (acute), A positive modulation of the inhibitory contents in the wound fluid, there is an induction of cell proliferation (in vitro and animal studies only), reduction of oedema and bacterial clearance, removal of exudates. 8 In short it is a fact that VAC therapy, is a faster more effective and clinically proven wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…13 The application of vacuum assisted closure is rising with advancing technology. Vacuum is seen to significantly decrease the surface area of wounds as compared to the daily dressing therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A number of clinical studies, both on animals and humans have been done so far. Most of these studies have reported the use of VAC as at par and at times better with the conventional wound closure techniques [ 16 ]. Argenta and Morykwas in the year 1997 reported the results of their study on 300 human subjects of which 296 patients responded favorably to the VAC [ 4 ].…”
Section: Commentarymentioning
confidence: 99%
“…The use of NPWT in the Indian studies has not been reported extensively. Only few Indian studies have provided insights into the NPWT use in Indian setting [ 16 , 44 - 46 ]. The NPWT using the VAC is definitely having an advantage in countries like India, where the patient load on the health centers is very high [ 47 , 48 ].…”
Section: Commentarymentioning
confidence: 99%